2011
DOI: 10.1186/1749-8090-6-53
|View full text |Cite
|
Sign up to set email alerts
|

LV reverse remodeling imparted by aortic valve replacement for severe aortic stenosis; is it durable? A cardiovascular MRI study sponsored by the American Heart Association

Abstract: BackgroundIn patients with severe aortic stenosis (AS), long-term data tracking surgically induced effects of afterload reduction on reverse LV remodeling are not available. Echocardiographic data is available short term, but in limited fashion beyond one year. Cardiovascular MRI (CMR) offers the ability to serially track changes in LV metrics with small numbers due to its inherent high spatial resolution and low variability.HypothesisWe hypothesize that changes in LV structure and function following aortic va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 21 publications
1
25
0
2
Order By: Relevance
“…The reverse remodelling changes observed following TAVI are consistent with the current SAVR literature4 24 and include new important observations. Similar levels of LV reverse remodelling occurred between transcatheter and surgical procedures except for small differences in end-diastolic volume (EDV) and EF.…”
Section: Discussionsupporting
confidence: 86%
“…The reverse remodelling changes observed following TAVI are consistent with the current SAVR literature4 24 and include new important observations. Similar levels of LV reverse remodelling occurred between transcatheter and surgical procedures except for small differences in end-diastolic volume (EDV) and EF.…”
Section: Discussionsupporting
confidence: 86%
“…In another study, including 45 patients with severe aortic stenosis, Poulsen et al (193) reported 20 and 31% decreases in LV mass index, 19 and 22% decreases in LV-end-diastolic volume, 31 and 31% decreases in LV end-systolic volume, and 6.3 and 6.3% increases in LV ejection fraction, 3 and 12 mo following AVR, respectively. Interestingly, other studies demonstrated that RR occurs mostly within the first 6 mo following AVR since 90% of the changes in cardiac volumes and ejection fraction are complete within this time frame (16) in which 75% of patients display a significant reduction of LV mass. However, a multivariate analysis showed that LV mass remained 5 SDs above normal for more than 85% of the population without an evident explanation based on the age, sex, coronary artery disease, and pre-AVR characteristics such as gradient, valve type, and cross-clamp time (16).…”
Section: Myocardial "Reverse Remodeling"mentioning
confidence: 95%
“…Interestingly, other studies demonstrated that RR occurs mostly within the first 6 mo following AVR since 90% of the changes in cardiac volumes and ejection fraction are complete within this time frame (16) in which 75% of patients display a significant reduction of LV mass. However, a multivariate analysis showed that LV mass remained 5 SDs above normal for more than 85% of the population without an evident explanation based on the age, sex, coronary artery disease, and pre-AVR characteristics such as gradient, valve type, and cross-clamp time (16). However, it is important to have in mind that in the clinical setting of HFpEF patients with compound comorbidities diastolic dysfunction may occur independently of LVH.…”
Section: Myocardial "Reverse Remodeling"mentioning
confidence: 95%
“…Moreover, during the “evolutionary” phase of LVH in their experiment (4 weeks of pressure overload), collagen matrix remodeling was associated with an increase in “embryonic” type III collagen [29]. The relationship between the relative proportions of type I and III collagen and the Gd-based contrast kinetics has not been explored before.…”
Section: Discussionmentioning
confidence: 99%